Analisis Kemampuan Pemecahan Masalah Dan Kemampuan Berpikir Kreatif Matematika Siswa Melalui Penerapan Model Pembelajaran Berbasis Masalah Pada Siswa Kelas VIII SMP Jendral Sudirman Medan - Panjaitan, Hendrikson (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
This study aims to: 1) Improve students' mathematical problem solving skills taught using the Problem Based Learning model 2) To improve students' mathematical creative thinking skills taught using the Problem Based Learning model 3) Analyze the number of difficult indicators of problem solving and thinking abilities students' mathematical creative learning using the Problem Based Learning model. The subjects in this study involved 38 class VIII students of Jendral Sudirman Medan who were given the Problem Based Learning treatment in the 2022/2023 even semester with a total of 38 students. The results of the study show that: 1) Students' mathematical problem solving abilities with a problem-based learning model. There were 11 students with good abilities (28.94%), 8 students with good abilities (21.05%), and 19 students with less ability (50%). 2) While the students' mathematical creative thinking skills with a problem-based learning model. There were 8 students with high abilities (21.05%), 6 students with moderate abilities (23.68%), and 21 students with low abilities (55.26%). 3) Students who have high mathematical creative thinking skills with a score of 93.75 have good problem-solving abilities with a score of 93.75. Students who have moderate creative thinking with a score of 75 have sufficient problem-solving abilities with a score of 68.75. And students who have low creative thinking with a score of 43.75 have less categorical problem solving abilities with a score of 50.